Developing a Web-Based Printing Transaction System Using The Prototype Method: A Case Study at Amanah Advertising - Annisa Dita Putri Kartika; Anindo Saka Fitri; Nambi Sembilu (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Digital transformation is increasingly vital for micro, small, and medium enterprises (MSMEs), including those in the printing sector, to enhance their operational effectiveness. Prior to this study, Amanah Advertising managed its orders, transactions, and inventory manually, which frequently resulted in data recording errors and poor coordination. To address these challenges, this research developed a web-based transaction management information system using the Prototype method. The development process involved two iterative stages of user feedback to refine system functionality. Enhancements included the addition of key features, improvements to the user interface, and the implementation of discount management functionality. The system was developed using the CodeIgniter 4 framework to ensure better process integration and operational efficiency. Black-box testing validated that all system components functioned correctly. Furthermore, a User Acceptance Testing (UAT) evaluation using a Likert scale produced a feasibility score of 85.2%, categorized as “Very Good.” These findings indicate that the implemented system significantly improves operational efficiency, increases data accuracy, and successfully supports the digitalization efforts at Amanah Advertising.